Analysis of reduction of particulate matter concentration and size distribution of di diesel engine by seawater spray - Pramnath, Ravi (2012)
Air pollution is a major environmental problem in most of the developing countries in the world. Air pollution is largely contributed as a consequence of the combustion of fossil fuels. Air pollutants are able not only to cause harm to our health but also to our environment. The after combustion or exhaust by the internal combustion engines, especially by compression ignition (CI) engines produces a complex mixture of pollutants that comprises both primary emissions, such as diesel soot particles, lead and sulfate particles formed from the burning of sulphur-containing fuel. The aim of this project is to measure reduction of diesel particulate matter (DPM) by diesel engine experiment using seawater spray and to utilize natural seawater. The diesel engine experiment was conducted with YANMAR TF120M single cylinder four stroke direct injection diesel engine set-up at variable engine speed namely at 2400, 2100, 1800, 1500 and 1200 rpm with and without seawater spray. An average of 26.1 % of DPM, 27.8 % of SOF and 19.5 % of DS has been reduced by using the seawater spray system. Overall DPM diameter size distribution able to be reduced.